Le développement du tourisme au Maroc : une perspective historique - Nidal Raffali (Études Caribéennes)
Although tourists had been visiting Morocco before the nineteenth century, modern tourism, as we know, if today only began during the Protectorate period. Before 1914, tourists entered Morocco through various ports of the country using steam-powered ships. Most tourists remained along the Moroccan coastline, with only a few exploring the interior. Following Independence in 1956, the Moroccan state created the first Ministry of Tourism with the intent of developing tourism in the country. This essay traces the historical development of tourism in Morocco and examines increasing tourism accessibility to the various geographical zones of the country.